2014
DOI: 10.1080/09670874.2014.956355
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of imidacloprid combined with synergistic agents (Beichuang, Jiexiaoli) onMyzus persicae(Hemiptera: Aphididae)

Abstract: Myzus persicae is a well known aphid pest, which can transport plant viruses to plants of the nightshade/potato family, namely the Solanaceae, and other food crops. Our aim was to explore the effects of imidacloprid combined with synergistic agents (Beichuang and Jiexiaoli) on Myzus persicae. Different concentrations of imidacloprid combined with synergistic agents were used to treat M. persicae. Biological activity of M. persicae was analyzed under indoor conditions, and the control efficiency of the admixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…With insecticide-resistant pest populations becoming an ever-growing concern, the development of novel synergists is needed. For example, Haitao Chen reports that Beichuang substances and Jiexiaoli substances have synergistic activity with a number of bacteria and that Beichuang substances and Jiexiaoli substances exert synergistic activities by affecting the contact angle and surface tension [ 11 ]. Gaofeng Cui reported that curcumin has synergistic activity with avermectin through the enhancement of programmed cell death [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…With insecticide-resistant pest populations becoming an ever-growing concern, the development of novel synergists is needed. For example, Haitao Chen reports that Beichuang substances and Jiexiaoli substances have synergistic activity with a number of bacteria and that Beichuang substances and Jiexiaoli substances exert synergistic activities by affecting the contact angle and surface tension [ 11 ]. Gaofeng Cui reported that curcumin has synergistic activity with avermectin through the enhancement of programmed cell death [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous field experiments have reported that insecticide efficacy can be increased substantially when adjuvants are added (Aioub et al, 2015; Chen et al, 2014; Demkovich et al, 2018). In viticulture, the use of adjuvants is regarded as a major mechanism for improving the efficacy of biological control agents (BCA) used against grape diseases to increase cell adherence to berry and leaf surfaces, leading to BCA establishment (Calvo‐Garrido et al, 2018).…”
Section: Introductionmentioning
confidence: 99%